Evaluations and Perceptions of the Climate Change in the State of Veracruz (Mexico): An Overview - Tejeda-Martínez, Adalberto; Torres-Alavez, J. Abraham; Ruiz-Barradas, Alfredo; Miranda-Alonso, Saúl; Salazar-Lizán, Sonia (IntechOpen, 2011)
None